2016
DOI: 10.1016/j.rppede.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Association between fat mass index and fat-free mass index values and cardiovascular risk in adolescents

Abstract: Objective:To describe the association between fat mass index and fat-free mass index values and factors associated with cardiovascular risk in adolescents in the city of Juiz de Fora, Minas Gerais.Methods:Cross-sectional study was with 403 adolescents aged 10–14 years, from public and private schools. Anthropometric, clinical, and biochemical measurements were obtained, as well as self-reported time spent performing physical exercises, sedentary activities and sexual maturation stage.Results:Regarding the nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…It is also noteworthy the strong correlation found between VAI, BF% and FFBI, in the MUH group, and the highest means of these variables, observed in adolescents with inadequate phenotype. These data corroborate with results demonstrated by Oliveira et al [47] who, when analyzing factors related to cardiometabolic risk in adolescents, identified that the overweight group had a higher FFBI when compared to subjects with adequate BMI and WC. This characteristic can be justified by behavioral changes, such as decreased level of physical activity and poor eating habits, in addition to changes in glucose and lipid metabolism, which are common during adolescence [48,42].…”
Section: Discussionsupporting
confidence: 92%
“…It is also noteworthy the strong correlation found between VAI, BF% and FFBI, in the MUH group, and the highest means of these variables, observed in adolescents with inadequate phenotype. These data corroborate with results demonstrated by Oliveira et al [47] who, when analyzing factors related to cardiometabolic risk in adolescents, identified that the overweight group had a higher FFBI when compared to subjects with adequate BMI and WC. This characteristic can be justified by behavioral changes, such as decreased level of physical activity and poor eating habits, in addition to changes in glucose and lipid metabolism, which are common during adolescence [48,42].…”
Section: Discussionsupporting
confidence: 92%
“…However, these authors considered body fat indexes above 25% for boys and 30% for girls 7 as a parameter for obesity 7 , whereas in this study, it was considered Above the Ideal at 20% and 25%, respectively. On the other hand, the results found in the present study are similar to those of a study carried out in southeastern Brazil that evaluated 403 adolescents between 10 and 14 years of age that detected overweight in 30.1% of those evaluated in both sex 19 .…”
Section: Discussionsupporting
confidence: 91%
“…However, researchers mostly agree on the high level of precision that the FMI must diagnose adipose hypertrophy with. High FMI has been correlated in teens with hypertriglyceridemia, high risk of cardiac disease, and elevated waist circumference [17].…”
Section: Fat Mass Index As a Diagnostic Toolmentioning
confidence: 99%